The Role of Lonp1 on Mitochondrial Functions during Cardiovascular and Muscular Diseases - Giada Zanini; Valentina Selleri; Mara Malerba; Kateryna Solodka; Giorgia Sinigaglia; Milena Nasi; Anna Vittoria Mattioli; Marcello Pinti (MDPI AG, 2023)
The mitochondrial protease Lonp1 is a multifunctional enzyme that regulates crucial mitochondrial functions, including the degradation of oxidized proteins, folding of imported proteins and maintenance the correct number of copies of mitochondrial DNA. A series of recent studies has put Lonp1 at the center of the stage in the homeostasis of cardiomyocytes and muscle skeletal cells. During heart development, Lonp1 allows the metabolic shift from anaerobic glycolysis to mitochondrial oxidative phosphorylation. Knock out of Lonp1 arrests heart development and determines cardiomyocyte apoptosis. In adults, Lonp1 acts as a cardioprotective protein, as its upregulation mitigates cardiac injury by preventing the oxidative damage of proteins and lipids, and by preserving mitochondrial redox balance. In skeletal muscle, Lonp1 is crucial for cell development, as it mediates the activation of PINK1/Parkin pathway needed for proper myoblast differentiation. Skeletal muscle-specific ablation of Lonp1 in mice causes reduced muscle fiber size and strength due to the accumulation of mitochondrial-retained protein in muscle. Lonp1 expression and activity decline with age in different tissues, including skeletal muscle, and are associated with a functional decline and structural impairment of muscle fibers. Aerobic exercise increases unfolded protein response markers including Lonp1 in the skeletal muscle of aged animals and is associated with muscle functional recovery. Finally, mutations of Lonp1 cause a syndrome named CODAS (Cerebral, Ocular, Dental, Auricular, and Skeletal anomalies) characterized by the impaired development of multiple organs and tissues, including myocytes. CODAS patients show hypotonia and ptosis, indicative of skeletal muscle reduced performance. Overall, this body of observations points Lonp1 as a crucial regulator of mitochondrial functions in the heart and in skeletal muscle.